Management of Mandibular Cholesterol Granuloma by Surgical Enucleation with Packing: A Rare Case Report - Al-Mousawi, Saif Nabil Jawad (Al-Rafidain Journal of Medical Sciences ( ISSN 2789-3219 ), 2025)
Cholesterol granuloma is a rare clinical entity described as inflammatory granulation in response to the deposit of cholesterol crystals. It can develop in any portion of air cells within the temporal bone as a result of a lack of aeration and adequate drainage. Here, we report a 65-year-old edentulous male with a painless slight expansion on the lower right body of the mandible, with a history of previous multiple lower denture constructions. A panoramic radiograph showed a well-defined unilocular radiolucency on the right body region of the mandibular bone. An incisional biopsy was done, then the lesion was completely enucleated surgically with packing, and the final diagnosis was confirmed by a histopathological examination report.